2021
DOI: 10.9734/jpri/2021/v33i37b32028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Awareness Regarding Heavy Metal Toxicity in School Children

Abstract: Background: Heavy metal toxicity is increasing rapidly due to the increased use of products containing heavy metals daily life. It can cause acute or chronic toxicity if they used for long term unknowingly especially by the children. Objectives: To assess whether the school children have information about products containing heavy metal which are used in daily life and their hazardous effects with the help of structured questionnaire. To sensitize the school children about the products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…White blood cell count was also abnormal in exposed group [18]. Different studies conducted among medical students on various health issues are available [19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 96%
“…White blood cell count was also abnormal in exposed group [18]. Different studies conducted among medical students on various health issues are available [19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 96%
“…It is crucial to aware the community about the early signs and symptoms of chronic kidney disease. (13)(14)(15)(16)(17)(18)(19)(20)(21) A scientific study was done in 2018 regarding the relation between chronic kidney disease and cognitive functions and found out that vascular injury can be a major cause of it. The deposition of calcium in the blood vessels makes the blood vessels stiff calcification appears.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acyanotic and cyanotic high-flow lesions, as well as those with pulmonary stenosis, should be treated by doctors with a high index of suspicion for the development of pulmonary tuberculosis. (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Rana Olguntürk, F.Sedef Tunaoğlu, Levent Gökgöz, Leyla Memiş, and Serdar Kula et al reported after seeing clinical improvement, the patient had surgery. The tricuspid valve underwent ringplasty, and the atrial septal defect was repaired.…”
Section: Discussionmentioning
confidence: 99%